Outcome of Apparently Unexplained Cardiac Arrest: Results From Investigation and Follow-Up of the Prospective Cardiac Arrest Survivors With Preserved Ejection Fraction Registry. (January 2016) - Herman, Adam R.M.; Cheung, Christopher; Gerull, Brenda; Simpson, Christopher S.; Birnie, David H.; Klein, George J.; Champagne, Jean; Healey, Jeffrey S.; Gibbs, Karen; Talajic, Mario; Gardner, Martin; Bennett, Matthew T.; et al.
Abstract : Background—: The Cardiac Arrest Survivors with Preserved Ejection Fraction Registry (CASPER) enrolls patients with apparently unexplained cardiac arrest and no evident cardiac disease to identify the pathogenesis of cardiac arrest through systematic clinical testing. Exercise testing, drug provocation, advanced cardiac imaging, and genetic testing may be useful when a cause is not apparent. Methods and Results—: The first 200 survivors of unexplained cardiac arrest from 14 centers across Canada were evaluated to determine the results of investigation and follow-up (age, 48.6±14.7 years, 41% female). Patients were free of evidence of coronary artery disease, left ventricular dysfunction, or evident repolarization syndromes. Advanced testing determined a diagnosis in 34% of patients at baseline, with a diagnosis emerging during follow-up in 7% of patients. Of those who were diagnosed, 28 (35%) had an underlying structural condition and 53 (65%) had a primary electric disease. During a mean follow-up of 3.15±2.34 years, 23% of patients had either a shock or an appropriate antitachycardia pacing from their implantable cardioverter defibrillator, or both. The implantable cardioverter defibrillator appropriate intervention rate was 8.4% at 1 year and 18.1% at 3 years, with no clear difference between diagnosed and undiagnosed subjects, or between those diagnosed with a primary electric versus structural pathogenesis. Conclusions—: Obtaining a diagnosis in previously unexplained cardiac arrest patients requires systematic clinical testing and regular follow-up to unmask the cause. Nearly half of apparently unexplained cardiac arrest patients ultimately received a diagnosis, allowing for improved treatment and family screening. A substantial proportion of patients received appropriate implantable cardioverter defibrillator therapy during medium-term follow-up. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00292032. Abstract : Supplemental Digital Content is available in the text.